Employee-athletes: exploring the elite Spanish athletes' perceptions of combining sport and work - Moreno, R.; Chamorro, J. L.; López de Subijana, C. (Frontiers in Psychology, 2021)
Researchers have studied the athletes' dual careers with the aim of helping them to combine the sport and the academic-vocational sphere. Most of this research has addressed the study-sport combination, but there is a lack of studies on the work-sport combination. The main objective of this research was to explore the subjective perceptions of Spanish elite athletes when attempting to combine their careers as professional athletes with a second profession or trade. Further, this study aims to identify the access to facilitating resources and the perception of obstacles and barriers to the development of a dual career. A qualitative approach was chosen to address these research questions. Interpretative phenomenological analysis was carried out on a sample of 18 elite athletes, and the data were collected using semi-structured interviews based on a set of superordinate and subordinate categories. The results showed that the athletes interviewed possessed valuable resources such as the transference of sports values to the work sphere. However, important barriers were highlighted such as the perception of sport institutions as absent entities in the work-sport combination. Thus, the study of this type of dual career seems to be one of the challenges facing the interested scientific community for the coming years.